Pengaruh E-Governance Terhadap Adaptabilitas Organisasi atas Implementasi Sistem Manajemen Pemeriksaan - Bayu Nugroho (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2014)
Adaptability in terms of the application of IT organizations is the ability to adapt to the application of IT by an organization, are relevant in the context of IT governance, business governance and strategic alignment . BPK adaptability in the use of SMP implementation will run well when done harmonization of key business processes related to unify the management and integration of all phases of inspection activities . This study aims to determine the effect of IT governance, business governance , and managerial capabilities of IT to BPK adaptability in the application of SMP . This study used a research model developed by Heart et al in 2010 . Analyst method used is Lisrel 8.80 . The results show that IT governance does not affect the managerial capabilities of IT , as well as business governance has no effect on the adaptability of the organization in implementing IT . In addition, the BPK also has a pretty good level of adaptability in the application of SMP.